A Fourier Ptychographic Microscopy Reconstruction Method Based on SwinIR Physical Model. Issue 1 (1st December 2022) - Wang, Xiaoli; Piao, Yan; Jin, Yuanshang; Li, Jie; Han, Qiuyue; Yu, Jinyang
Abstract: Fourier ptychographic microscopy (FPM) computational imaging is a newly developed microscopic computational imaging technology in recent years, which can realize large field-of-view (FOV) and high-resolution microscopic imaging. In this paper, the SwinIR physical model is introduced to solve the problems of a slightly long reconstruction time and poor reconstruction effect of the FPM reconstruction algorithm based on physical learning. Different from the traditional CNN network structure, this physical model completes the reconstruction of images by introducing modular design and feature fusion. Through a series of simulation experiments on ideal images and real images, it is proved that the reference physical model has better reconstruction quality than the comparison algorithm.